Wenshenyang recipe treats infertility through hormonal regulation and inflammatory responses revealed by transcriptome analysis and network pharmacology - Xie, Lan; Zhao, Shuai; Zhang, Xiaoling; Huang, Wenting; Qiao, Liansheng; Zhan, Delin; Ma, Chengmei; Gong, Wei; Dang, Honglei; Lu, Hua (Frontiers in Pharmacology, 2022)
The Wenshenyang recipe (WSYR) has the effect of treating infertility, but the mechanisms underlying this activity have not been fully elucidated. In this study, network pharmacology and RNA sequencing were combined, with database-based “dry” experiments and transcriptome analysis-based “wet” experiments used conjointly to analyse the mechanism of WSYR in the treatment of infertility. In the dry analysis, 43 active compounds in WSYR and 44 therapeutic targets were obtained through a database search, 15 infertility pathways were significantly enriched, and key targets, such as ESR1, TP53, AKT1, IL-6, and IL-10 were identified. In the wet experimental analysis, HK-2 cells were treated with the three herbs of WSYR. Using the transcriptome sequencing platform, the expression level changes in 412 genes from 15 infertility pathways were observed, and 92 DEGs were finally obtained. Additionally, key targets, such as ESR2, STAT1, STAT3, and IL6, were identified. RT-qPCR experiments further verified that WSYR played an anti-inflammatory role by upregulating IL-4 and IL-10. By building the molecular docking model of ESR1, ESR2 and screening compounds, it was further found that xanthogalenol in Gusuibu, arachidonate in Roucongrong, and anhydroicaritin in Yinyanghuo have good affinity for estrogen receptors. These findings provide evidence that WSYR exerts an estrogen-regulating role. By integrating the results of dry and wet experiments, it was found that the WSYR treats infertility by regulating hormone levels and inflammatory responses.